1966
DOI: 10.1111/j.1365-2621.1966.tb15422.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and Chemistry of Fermented Fish

Abstract: Microbiology SUMMARYThe microbiology and chemistry of Thai fish sauce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 9 publications
2
82
0
1
Order By: Relevance
“…The predominance of Bacillus species in the microflora of fermented fish sauce has been reported by Saisithi et al (1966), Crisan and Sands (1975) and Beddows (1985). However, Thongthai and Siriwongpairat (1990) …”
Section: Generic Distribution Of Bacteria In Different Treatments Durmentioning
confidence: 90%
“…The predominance of Bacillus species in the microflora of fermented fish sauce has been reported by Saisithi et al (1966), Crisan and Sands (1975) and Beddows (1985). However, Thongthai and Siriwongpairat (1990) …”
Section: Generic Distribution Of Bacteria In Different Treatments Durmentioning
confidence: 90%
“…It has been reported that the aroma of fish sauce is composed of a blend of ammoniacal, cheesy and meaty notes.1) A variety of amines, ammonia and other nitrogen containing compounds have been attributed to the ammoniacal note as described by Dougan and Howard and Saisithi et al 2 ) Truong Van Chom 3 ) considered volatile fatty acids such as formic, acetic and n-butanoic acids as contributory factors in the aroma of fish sauce. Investigation of Noucmam, a Vietnamese fish sauce revealed that it contains a large amount of methyl ketones which probably accounts for the cheesy odor.…”
mentioning
confidence: 99%
“…Though it is quite popular, no studies have been done to determine the spectrum of micro-organisms associated with the spontaneous fermentation of poo-khem. However, halophilic or halotolerant members of the genus Bacillus are likely to be the most prevalent species and to persist until the end of the fermentation, a situation similar to that found for other salted fishery products such as fish sauce and krill paste (Saisithi et al, 1966;Crisan & Sands, 1975;Yoon et al, 2001;Noguchi et al, 2004). In this study, a Gram-positive, rod-shaped bacterium, strain PD-A10 T , isolated from pookhem, was characterized by means of a polyphasic taxonomic approach and compared with other recognized species.…”
mentioning
confidence: 99%